Chasing newsroom diversity : from Jim Crow to affirmative action - Mellinger, Gwyneth (History of communication., 2013)
Social change triggered by the Civil Rights Movement in the 1960s sent the American Society of Newspaper Editors (ASNE) on a fifty-year mission to dismantle an exclusionary professional standard that envisioned the ideal journalist as white, straight, and male. In this book, the author explores the complex history of the decades-long ASNE diversity initiative, which culminated in the failed Goal 2000 effort to match newsroom demographics with those of the U.S. population. Explaining why a project so promising failed so profoundly, this book expands our understanding of the intransigence of institutional racism, gender discrimination, and homophobia within democracy. -- Publisher's description.